Exosomes As A Revolutionary Tool In Wound Healing And Skin Regeneration: Current Evidence And Therapeutic Potential - Dandoulakis, MD, Emmanouil (Journal of Neonatal Surgery, 2025)
Nano-sized extracellular vesicles, such as the exosomes, innovate wound healing and skin regeneration based on intercellular crosstalk via bioactive payloads (miRNA, proteins, lipids). This review outlines the ability of these compounds to accelerate wound healing, mitigate inflammation, and promote tissue remodeling, as well as recent findings from preclinical and clinical trials. Discoveries, such as exosome-derived biomaterials, including hydrogels, and targeted delivery systems, like CRISPR-engineered exosomes, enhance the efficacy of therapeutics. The existence of rare and exciting discoveries validates the future of transformative possibilities, including hypoxic-conditioned exosomes that stimulate HIF-1α and plant exosomes that enhance burn healing, such as those derived from ginger. Preliminary data indicate that mesenchymal stem cell-derived exosomes can improve healing rates by up to 30-50% in diabetic models, and early-phase clinical studies suggest a decrease in scarring and chronic wound inflammation in chronic wounds. Exosomes have significant clinical and translational potential in the treatment of chronic wounds, burns, and aesthetic dermatology, meeting the demand for biocompatible, low-immunogenicity products. These advances make exosomes a transformative type of regenerative medicine, marking a breakthrough in personalized and scalable applications of wound care and skin regeneration despite the challenges of scalability and standardization.